2004
DOI: 10.1149/1.1690293
|View full text |Cite
|
Sign up to set email alerts
|

Etching AlAs with HF for Epitaxial Lift-Off Applications

Abstract: The epitaxial lift-off process allows the separation of a thin layer of III/V material from the substrate by selective etching of an intermediate AlAs layer with HF. In a theory proposed for this process, it was assumed that for every mole of AlAs dissolved three moles of H 2 gas are formed. In order to verify this assumption the reaction mechanism and stoichiometry were investigated in the present work. The solid, solution and gaseous reaction products of the etch process have been examined by a number of tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 10 publications
1
51
0
1
Order By: Relevance
“…15 It was found that the reaction between AlAs and the HF etchant is most likely described by a set of overall reactions given by…”
mentioning
confidence: 99%
“…15 It was found that the reaction between AlAs and the HF etchant is most likely described by a set of overall reactions given by…”
mentioning
confidence: 99%
“…The attack of the substrate by the HF and the residues formed during the sacrificial layer etching result in the increase of RMS roughness from 0.3 to 1-4 nms range. Chemical reactions between AlAs and HF have been well studied 10,15,16 6 À n ] (3 À n) þ , on the other hand, are solid and hard to dissolve into the solution. Besides these primary byproducts, solid As 2 O 3 can also be generated on the substrate depending on the oxygen concentration of the etchant 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, developing a new ELO process with different chemistry that enables the direct reuse of the substrate is very desirable to lower the overall cost. Although HCl-based etchant was proposed and used by several researchers to selectively etch AlGaAs 10,11 or other sacrificial layers [12][13][14] , the possibility of reusing the substrate directly with these methods has not been explored. In this paper, we demonstrate a new ELO process where aluminium-arsenide based sacrificial layer and HF-based etchant are replaced with phosphide-based materials and HCl.…”
mentioning
confidence: 99%
“…Since a basic wet chemical smoothing etch procedure appeared insufficient to remove all surface contamination, wafer re-preparation is done by a surface cleaning followed by a chemomechanical polishing procedure. Multiple wafer re-use without degradation in solar cell quality was shown using this procedure [4]. .…”
Section: Figure 2 Two Elo Set-ups Developed At Radboudmentioning
confidence: 95%
“…We have tested a number of different set-ups for ELO ( fig.2) [3] and investigated the mechanism of the etch process in detail [4,5].…”
Section: Epitaxial Lift Offmentioning
confidence: 99%